2022
DOI: 10.1186/s12909-022-03141-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of non-bedside teaching during the COVID-19 pandemic: a quasi-experimental study

Abstract: Background The COVID-19 pandemic poses a huge challenge for clinical teaching due to contact restrictions and social distancing. Medical teachers have to balance potential risks and benefits of bedside teaching, especially in course formats intended to foster practical clinical skills. In this context, we aimed to address the question, whether presence-based teaching formats without patient involvement are suitable to teach practical skills. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…In another research, while analyzing the impact of face-to-face teaching in addition to electronic learning, Currat et al (2022) showed that live teaching improved skill acquisition and enhanced skill retention. Contrary to the stated finding, another study (Heitmann et al, 2022) examined the lecturer ratings of student's theoretical knowledge and practical skills in two clinical teaching formats, with and without patient contact, where the group without patient contact was rated significantly better by the lecturers. On the other hand, students expressed negative views on teaching format without patient contact and commented that lack of contact with patient during the course hampers their ability to apply the practical skills acquired in a clinical context.…”
Section: The Main Findingsmentioning
confidence: 88%
“…In another research, while analyzing the impact of face-to-face teaching in addition to electronic learning, Currat et al (2022) showed that live teaching improved skill acquisition and enhanced skill retention. Contrary to the stated finding, another study (Heitmann et al, 2022) examined the lecturer ratings of student's theoretical knowledge and practical skills in two clinical teaching formats, with and without patient contact, where the group without patient contact was rated significantly better by the lecturers. On the other hand, students expressed negative views on teaching format without patient contact and commented that lack of contact with patient during the course hampers their ability to apply the practical skills acquired in a clinical context.…”
Section: The Main Findingsmentioning
confidence: 88%
“…Interestingly, previous studies indicated that face-toface teaching formats with patient contact were rated signi cantly higher by students compared to nonface-to-face teaching, but that there was no particular difference in students' knowledge and skill development compared to non-face-to-face learning. 2) The availability of various types of educational methods in the medical eld should be utilized to create different learning frameworks, including online education, depending on the educational content, in order to increase learning e ciency within a limited amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…They experienced a limited session of clinical supervision from lecturers [ 16 ]. As a result, this phenomenon significantly causes medical students to get lower grades than expected grades [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They experienced limited session of clinical supervision from lecturers 16 . Consequently, this phenomenon signi cantly affected to the less grade of medical students 17 .…”
Section: Introductionmentioning
confidence: 99%